Facile synthesis of 3-substituted imidazo[1, 2-a]pyridines through formimidamide chemistry. Issue 51 (19th September 2019) - Sivappa, Rasapalli; Sammeta, Vamshikrishna Reddy; Huang, Yanchang; Golen, James A.; Savinov, Sergey N.
Abstract : A facile entry to 3-substituted imidazo[1, 2- a ]pyridines from halides and 2-amino pyridines via formimidamide chemistry has been developed through a formal anti-Baldwin 5-endo-trig cyclization that becomes a thermally allowed 5-exo-trig cyclization. Abstract : A facile entry to 3-aryl/alkenyl/alkynyl substituted imidazo[1, 2- a ]pyridines (3a–p, 6a–d & 9a–9e ) has been developed from readily available benzyl/allyl/propargyl halides and 2-amino pyridines as substrates via formimidamide chemistry that is devoid of caustic or expensive reagents, such as transition metal complexes. Quantum chemical calculations performed to understand the underlying mechanism of the transformation revealed a preference for intramolecular Mannich-type addition over pericyclic 1, 5-electrocyclization for the systems reported herein that enable a Baldwin allowed 5- exo -trig cyclization instead of a formally anti-Baldwin 5- endo -trig process.